2010
DOI: 10.1021/es101072s
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Nanosilver Ions and Particles

Abstract: The antibacterial activity of nanosilver against Gram negative Escherichia coli bacteria is investigated by immobilizing nanosilver on nanostructured silica particles and closely controlling Ag content and size. These Ag/SiO(2) nanoparticles were characterized by S/TEM, EDX spectroscopy, X-ray diffraction the exposed Ag surface area was measured qualitatively by O(2) chemisorption. Furthermore, the fraction of dissolved nanosilver was determined by measuring the released (leached) Ag(+) ion concentration in aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

28
632
1
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 755 publications
(664 citation statements)
references
References 27 publications
28
632
1
3
Order By: Relevance
“…Mahmoodzadeh et al (2013) reported that direct exposure to specific types of nanoparticles causes significant phytotoxicity, emphasizes the need for ecologically responsible disposal of wastes containing nanoparticles and also highlights the necessity for further study on the impacts of nanoparticles on agricultural and environmental systems. The toxicity of AgNPs has been investigated in different terrestrial and aquatic organisms and was found to be related to their bioaccumulation effect of silver (Georgios & Sotiris, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Mahmoodzadeh et al (2013) reported that direct exposure to specific types of nanoparticles causes significant phytotoxicity, emphasizes the need for ecologically responsible disposal of wastes containing nanoparticles and also highlights the necessity for further study on the impacts of nanoparticles on agricultural and environmental systems. The toxicity of AgNPs has been investigated in different terrestrial and aquatic organisms and was found to be related to their bioaccumulation effect of silver (Georgios & Sotiris, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to differentiate between antibacterial effects of ionic silver and Ag nanoparticles as all nanoparticles release a degree of silver ions [15,16]. The antimicrobial effect of silver is thought to be the combination of several mechanisms of action; for example, silver ions and small silver nanoparticles (Ag-NPs) (less than 10nm) have been shown capable of entering the bacterial cytoplasm and inhibit cell growth [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, many adverse toxicological effects on living organisms are still reported. Generally, it is recognized that toxicity and antibacterial activity are related to the release of Ag+ ions from the Ag NPs [6] but the efficiency of these effects can be modulated by the NPs uptake or the interaction of NPs with different biological compartments [7,8]. Colloidal aqueous suspension of spherical Ag NPs of 7-20 nm induce cytotoxicity on primary mouse fibroblasts and primary liver cells; moreover they induce oxidative stress as reduction in the glutathione (GSH) level, and increase of reactive oxygen species (ROS) and lipid peroxidation on human skin carcinoma cells (A431) and human fibrosarcoma cells (HT-1080) [9,10].…”
Section: Introductionmentioning
confidence: 99%